Is it true that Non-Performing Financing is a Risk Mitigation effort? - jumaiyah jumaiyah; Wahidullah Wahidullah (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2023)
Distribution of financing to customers is inseparable from various risks, such as failure of financing, as evidenced by repeated arrears in paying credit. Various efforts were made to save the health of the Sharia People's Financing Bank (BPRS). The purpose of this study is to determine effective and efficient non-performing financing (NPF) settlement strategies for murabahah financing and the obstacles encountered in completing NPF murabahah financing as a risk mitigation effort. The method used is a qualitative approach with a field approach. The data collected is primary and secondary data for 2020–2022, using observation, interview, and documentation techniques. The results of the first study show that non-performing murabahah financing continues to increase. In 2020, 5%, in 2021, 10%, and in 2022, 14% Second, if there are indications of a problem with murabahah financing being stuck, it is resolved through a personal approach by deliberation, routine billing via telephone or WhatsApp, home billing, and 3 warning letters. If there is a response or good faith, restructuring is carried out through restructuring, rescheduling, and reconditioning, and if with this step the customer has no ability to complete the financing, the sale of collateral will be carried out. Meanwhile, if the settlement steps have been taken but the customer has no response or no good faith, then the sale of collateral items is carried out and a simple lawsuit is filed with the Religious Courts. The three obstacles encountered in completing murabahah financing, namely customers disappearing or running away by going out of town, lack of understanding of customers regarding financing restructuring, customers deliberately removing goods or vehicles that are used as collateral objects, and customers who always show rude attitudes or behavior, have to be approached many times and definitely require a lot of energy, time, and money.